The need for the implementation of an Ecosystem Services assessment in Greece: drafting the national agenda - Panayotis Dimopoulos; Evangelia Drakou; Ioannis Kokkoris; Stelios Katsanevakis; Athanasios Kallimanis; Maria Tsiafouli; Dimitrios Bormpoudakis; Konstantinos Kormas; Jeroen Arends (One Ecosystem, 2017)
This paper presents the establishment and the first outcomes of the Hellenic Ecosystem Services Partnership (HESP), a scientific-technical committee aiming at the guidance and coordination of the Ecosystem Services (ES) assessment in Greece. HESP consists of experts from different disciplines (ecology, marine biology, socio-ecological system science) and aims to: i) coordinate ES assessment efforts under a shared framework; ii) promote the ES approach in Greece; iii) support the European implementation of ES at the national level (Mapping and Assessment of Ecosystem and their Services initiative), and iv) fulfill priority actions regarding the ES implementation and the obligations derived from the National Biodiversity Strategy. In this paper, we present the first drafting of the National Agenda including short- and long-term objectives towards the national implementation of MAES, we outline the HESP Action Plan to 2020, as well as the timeline of the basic steps to be taken, to achieve decision making on the basis of ES maintenance and enhancement. It will also serve as a call for action to encourage more ES assessments at the national level, but also as a primer for the inclusion of protected areas and other areas of special importance for ES assessments at the EU level.